Sosialisasi Anti-Bullying Kepada Siswa Sekolah Dasar Negeri 16 Kayu Agung - Indriyana Setyawati; Ela Amalia; Galih Andi Prabowo; Mgs Alfin Kurniawan; Indah Lestari; Karsma Kapur; Nabila Farisya; Kinanti Putri Sysynovani; Fitri Larasati; Shela Maharani; Riski Arya; Mayda Yulistia; Hesty Wulandari; Lastari Apriana; Sabda Wahab (JURNAL PENGABDIAN KADER BANGSA, 2026)
Bullying in elementary schools remains a problem that can impact students' psychosocial development and learning process. Various studies indicate that approximately 20–30% of school-age children have been involved in bullying, either as victims, perpetrators, or witnesses. Initial observations at SDN 16 Kayuagung also identified indications of bullying behavior and the lack of structured anti-bullying outreach activities. This community service activity aimed to provide education on bullying prevention and increase students' understanding of its forms, impacts, and prevention methods. The activity was conducted with 62 fourth, fifth, and sixth grade students using a participatory educational method that included delivering material using PowerPoint presentations, providing case studies, singing anti-bullying songs, and a question-and-answer session. Evaluation was conducted using descriptive qualitative methods through participatory observation of student engagement and responses during the activity. Results showed a positive response from students and identified an increased understanding of the concept of bullying and the importance of maintaining respectful social behavior in the school environment. This outreach activity has the potential to be a preventative measure to support the creation of a safer and more child-friendly school environment.